Increased Defect Size is Associated with Increased Complication Rate after Free Tissue Transfer for Midanterior Skull-Base Reconstruction - Nakamura, Ryota; Takanari, Keisuke; Nakamura, Yutaka; Kambe, Miki; Hishida, Masashi; Ebisawa, Katsumi; Fujimoto, Yasushi; Fujii, Masazumi; Kamei, Yuzuru (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective Complications after skull-base reconstruction are often problematic. We consider that local factors, for example, localization of defect areas are possible risk factors. This study aimed to investigate our case series of skull-base reconstructions in our institution and to identify local risk factors that predispose to wound complications.Design This study is presented as a retrospective study.Setting Research work was took place at Nagoya University Hospital.Participants Forty-eight patients who had undergone reconstruction after midanterior skull-base resection between January 2004 and December 2015 were included in this study. Defects apart from the skull-base were categorized into nasal and paranasal cavity (N), orbit (O), palate (P), and facial skin (S). Postoperative local complications including cerebrospinal fluid (CSF) leakage, local infection, wound dehiscence (fistula in face or palate), and flap necrosis (partial or total) were investigated.Main Outcome Measures Main outcome measures were postoperative complications in patients with each defect.Results Apart from the skull-base, defects included 28 ONP (58.3%), 10 ONPS (20.8%), 3 ON (6.3%), 3 ONS (6.3%), 1 NP (2.1%), and 1 OS (2.1%). Comparison based on numbers of resected regions revealed that a significantly higher complication rate was seen in patients with four resected regions than in those with three regions (90.0% vs. 45.2%, p < 0.05).Conclusion There was a trend suggesting that more resected regions corresponded to a greater risk of complications in midanterior skull-base reconstruction. Reconstructive surgeons need to carefully consider the reconstruction of such complicated defects.
Keywords: Skull-base reconstruction; postoperative complication; microsurgery; free flap